The Impact of the Financial Budget on Exchange Rate Risk the Impact of the Financial Budget on Exchange Rate Risk - hantoosh, Mustafa Akram; Hakim, Hesham Talaat Abdel (Journal of Ecohumanism, 2025)
The research aims to determine the impact of the financial budget on exchange rate risk. Therefore, this research was designed with the aim of identifying the impact of the financial budget on exchange rate risk. This research included some theoretical concepts related to both the financial budget and exchange rate risk. The research period extended during the period (2023-2015). A set of financial methods were used to measure the research variables represented by the financial budget and exchange rate risk represented by (the gap between the official price and the parallel price). A set of statistical methods were also used to determine the impact between the variables and test the research hypothesis, including simple linear regression, in addition to using the interpretation coefficient (determination) (R2) for the purpose of measuring the percentage of what the independent variable explains of the changes affected by the dependent variable in the research. The significance test (F) to test the significance of the main research hypothesis, and in order to verify the proof of the research hypothesis, the statistical program (spss-V23) was relied upon. Some of the research conclusions indicated the absence of a statistically significant effect of the financial budget on exchange rate risk, which means that the financial budget does not have effect on exchange rate risk.